Adaptasi Siswa Terhadap Pembelajaran Pendidikan Pancasila dalam Kurikulum Merdeka - Nenia Nabila Patimah (Pusat Riset dan Inovasi Nasional, 2025)
The implementation of Merdeka Curriculum in learning Pancasila Education has brought major changes in the learning process at the high school level. This change requires students to adapt to a learning approach that is more focused on students (student centered learning). This study aims to analyze student adaptation in learning Pancasila Education in the Merdeka Curriculum at SMA Negeri 6 Serang City. The research method uses a descriptive qualitative approach with data collection through in-depth interviews. The results showed that the student adaptation process took place gradually, where students began to adapt to the demands of active learning which required them to be involved in building their own knowledge. In this adjustment process, students face several challenges. Despite facing various challenges, the impact of adjustment on learning outcomes shows positive progress.